MIGRASI AUSTRONESIA PROTOSEJARAH KE PULAU SAMOSIR DAN PERANNYA PADA KEBUDAYAAN DI WILAYAH SEKITARNYA - Ketut Wiradnyana (Balai Arkeologi Provinsi Sulawesi Utara, 2018)
Samosir Island in the middle of Lake Toba, a central area of Toba Batak culture. Prehistoric cultural aspect that is very prominent in the Batak Toba culture is a megalithic culture in the form of ancestor worship concept, container graves and various shades of decorative patterns. variety of shapes, materials and decorative patterns have in common with shades of megalithic culture in Sulawesi. Based on the cultural pattern that develops and research results in the area of prehistoric Austronesian in the surrounding area indicate that migration to the island of Samosir in the period Austronesian protohistory. The indicated migration of Sulawesi in the early AD. Since the Toba Batak society plays an important role in the cultural assimilation with the surrounding area. it can be determined based on the study of archaeological and ethnographic approach through deductive reasoning eksplanatif.